Pandemics, disasters, sustainability, tourism : an examination of impact on and resilience in Caribbean small island developing states - Bethell-Bennett, Ian; Rolle, Sophia; Minnis, Jessica; Okumus, Fevzi (Emerald Publishing Limited, 2022)
Caribbean small island developing states (SIDS) have witnessed great upheaval and change over the last decade and a half - from the global economic recession of 2008, the 2010 and 2021 earthquakes in Haiti, to hurricanes that devastated islands like Jamaica, Barbuda, Dominica and The Bahamas, volcanic eruptions, and health crises. These events are reminders of how vulnerable Caribbean SIDS are to external and internal shocks; today Caribbean SIDS are grappling with how to restart their economies and embrace a "new normal" in the wake of disasters and the sharp losses in tourism. Pandemics, Disasters, Sustainability, Tourism examines the resilience of Caribbean SIDS and their tourism industries from the perspectives of culture, economy, environment, politics, psychology, social justice, and socio-historical context. Pandemics, Disasters, Sustainability, Tourism's broad-based topics engage scholars, students, and the public in discourse regarding Caribbean SIDS' resilient Island economies that, facing calamity, implement new initiatives to forge environmentally sound policies for sustainable tourism and hospitality development.
Keywords: Tourism -- Caribbean Area.; Natural disasters -- Economic aspects -- Caribbean Area.; Financial crises -- Caribbean Area.; Caribbean Area -- Economic conditions -- 21st century.; Caribbean Area -- Social conditions -- 21st century.; elektronické knihy; electronic books